Marketing of Educational Services: A New Strategy for Customer Satisfaction - Prof. R. Veerappan, Dr. D. Maria Antony Raj, Dr. M. Raguraman (International Journal of Scientific Research and Management (IJSRM), 2013)
Students and the parents are aware that the cost of education has been on the rise irrespective ofmushroom growth of educational institutions. Already there is cutthroat competition among various privateeducational institutions. This competition will become more aggressive if the foreign universities are allowedto open their study centres in India. Albeit quality and employability are the main concerns of responsibleinstitutions, money minting institutions which aim high rate of return lure and divert the parents and thestudents through attractive ads, by bypassing customer satisfaction. However, the success of these institutionswill be possible only in the short run. Under these circumstances, building customer loyalty throughcustomer satisfaction has become a challenging one. A well designed educational marketing strategy is theneed of the hour for ensuring success and survival in the market. There are some key considerations-i.e.,Education should be Approachable, Applicable, Adaptable and Appraisable. These 4A’s should be the‘mantra’ of any educational institution for ensuring success in the market. Right communication strategy atthe right time can ensure easy approachability. Introduction of relevant and fresh curricula can guarantee theemployability of a student. Any system that is introduced should be adaptable. Otherwise, there will be totaldilution and the entire plan of the organisation will be collapsed. After adapting the scheme, it should beevaluated properly to know the results and identify the changes required for further improvement. This paperis an attempt to identify the strategy to be applied by the educational institutions in marketing their servicesin order to ensure their success and survival